Становление технологии Web 3.0 - Глибовец, Н.Н.; Шыпович, Л.О. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2010)
Проанализировано развитие Web-технологий и становление технологии Web 3.0. Выделены основные отличия технологии Web 3.0. Продемонстрировано использование новых подходов на примере создания Web-документа на базе онтологий объектов без HTML-разметки. In the paper Web and Web 3.0 technology development analysis is made. The main differences of Web 3.0 from the previous technologies are outlined. The usage of new approaches are demonstrated on a Webdocument creation on the basis of ontology objects without HTML-markups.